Morphometric characterization of purebred and crossbred Baoulé cattle in Burkina Faso. (1st October 2020) - Yougbaré, B.; Soudré, A.; Ouédraogo, D.; Zoma, B. L.; Tapsoba, A. S. R.; Sanou, M.; Ouédraogo-Koné, S.; Burger, P.; Wurzinger, M.; Khayatzadeh, N.; Tamboura, H. H.; Traoré, A.; et al.
ABSTRACT: A morphometric characterization study was conducted using purebred Baoulé cattle and two crossbreds' populations in the southwestern region of Burkina-Faso. A total of 421 cattle, including 266 crossbreds from the department of Kampti and Loropeni and 155 purebred Baoulé, from the department of Bouroum-Bouroum were measured for quantitative and qualitative traits. The quantitative traits were analyzed by fitting the linear model including genotype-location, sex, age and all two-way interactions. The chi square test was performed for qualitative traits. The results provide evidence for difference between purebred and crossbred populations, and among crossbreds for all traits. The genotype-location effect showed that facial length, distance between horn tips, ear length and chest width differed between purebred and crossbred populations. For qualitative traits, coat color and horn shape showed large variation between Baoulé and crossbreds. These results will serve as basis for further characterization, conservation and improvement strategies for purebred and crossbred populations.